EXPLORING THE PERCEPTIONS OF UNDERGRADUATE MEDICAL STUDENTS AND FACULTY REGARDING THEIR ENGAGEMENT IN INTEGRATED CURRICULUM DEVELOPMENT IN AZAD JAMMU & KASHMIR MEDICAL COLLEGE MUZAFFARABAD. - Muhammad Ijaz; Jamil, Brekhna; Nowshad Asim; Ayaz Ul Haq; Yasir Khan; Samreen Riaz (Journal of Ayub Medical College Abbottabad, 2024)
Background: The development of a medical curriculum is a multi-layered and complicated process, demanding teamwork among diverse stakeholders, including undergraduate medical students and faculty members. This study investigates the underexplored realm of stakeholder perceptions, specifically those of undergraduate medical students and faculty, regarding their engagement in the intricate process of medical curriculum development